Expository Learning Model in Islamic Religious Education - Adona, Putri; Dalimunthe, Halima (Fitrah, 2025)
The creation of effective learning is a result of the role that educators take in designing learning activities, including the selection of learning models to be used. Based on this point, in this research, the authors will explain the theory of expository learning model in PAI learning. The research method used refers to a qualitative approach, where the data is presented in narrative form related to the theory of expository learning model in PAI learning. The data sources of this research come from relevant books and articles, then analyzed using content analysis techniques to sort, identify, and conclude information from various literatures in order to give rise of different perspectives related to the expository learning model in PAI learning. From the analysis, the author found three sub-themes related to the expository learning model in PAI learning, which are: i) the concept of expository learning model, ii) the syntax of expository learning model, iii) the design of expository learning model in PAI learning. In the future, the author hopes that this research will have a positive impact, especially in the development of PAI learning models, so that students get a meaningful learning experience.